(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Digital banking is the automation of traditional banking services. Digital banking enables a bank’s customers to access banking products and services via an electronic/online platform. Digital banking means digitalizing all of the banking operations and substituting the bank’s physical presence with an everlasting online presence, eliminating a consumer’s need to visit a branch. Indian Government’s vision of a cashless economy and rapid development in improving internet availability throughout the nation, the country recorded over 48.6 billion real-time payment transactions in 2021 (the highest in the world) exceeding China. Digital banking services have made banking activities fast, hassle-free and highly efficient. As much as there are benefits to digital banking there are also problems with digital banking. This study has given problems of digital banking services among digital banking user in Tenkasi district. This research collected data from 715 digital banking users in Tenkasi district.